1998
DOI: 10.1002/(sici)1097-4628(19981031)70:5<935::aid-app14>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of readily processable thermoplastic‐toughened thermosets. II. Epoxy toughened using a reactive solvent approach

Abstract: The fracture toughness of epoxy thermosets was increased by up to 220% using very low-molecular-weight (ϳ 1000 g/mol) imide thermoplastic. The objective was to produce a low-viscosity prepolymer that could be easily autoclave-processed to give a tough thermoset. Here, an homogenous epoxy prepolymer was prepared by first synthesizing very low-molecular-weight linear aromatic imide (ϳ 1000 g/mol) directly in a liquid allyl phenol reactive solvent, followed by dissolution of the epoxy (Epon® 825) and the cure age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The results are shown in Figure . The coatings without and with Vi‐PDMS both showed a smooth surface, and the coatings with Vi‐PDMS were more opaque [Figure (a,b)] . The appearance further confirmed that phase separation occurred in the film‐formation process.…”
Section: Resultsmentioning
confidence: 74%
“…The results are shown in Figure . The coatings without and with Vi‐PDMS both showed a smooth surface, and the coatings with Vi‐PDMS were more opaque [Figure (a,b)] . The appearance further confirmed that phase separation occurred in the film‐formation process.…”
Section: Resultsmentioning
confidence: 74%